Suppression of Tumor Angiogenesis by Nonsteroidal Anti-Inflammatory Drugs: A New Function for Old Drugs - Curzio Raegg; Olivier Dormond (The Scientific World Journal)
There is solid epidemiological evidence demonstrating that the regular use of nonsteroidal anti-inflammatory drugs (NSAIDs) reduces the risk of developing colorectal cancer, and to a lesser extent gastric and esophageal cancers[1]. Importantly, NSAIDs suppress colon polyp formation and progression in patients diagnosed with familial adenomatous polyposis coli (APC)[2]. In many animal studies, NSAIDs have been shown to prevent tumor formation and slow tumor progression, thus confirming and extending the clinical observations[3,4,5]. Recent findings have demonstrated that NSAIDs inhibit angiogenesis, suggesting that the tumor suppressive activity of these drugs may be due, at least in part, to their ability to inhibit tumor angiogenesis[6]. The study of the mechanism by which NSAIDs suppress tumor angiogenesis, is matter of intense research.